DRY APRICOT BRANDY: DEVELOPMENT AND PHYSICOCHEMICAL CHARACTERIZATION OF A NEW BEVERAGE - Leite, Marcelo Teixeira; de Souza Pontes, Débora Telma (Seven Editora, 2025)
The global distilled beverage market has been influenced by a notable change in consumer behavior, which is increasingly looking for products with a differentiated flavor profile. In this context, fruit spirits have become an interesting option, due to the variety of flavors they can offer. The objective of this work was to produce a fruit brandy, using dried apricots as raw material. Dried apricots have an intense and unique flavor, which meets new consumer trends. For the production of this drink, initially a fermentation must was prepared that consisted of maceration water from the dried fruits. The wort was inoculated with a commercial strain of Saccharomyces cerevisiae and fermentation was conducted in a single-batch system, in a closed vessel equipped with airlock. The distillation was carried out in a copper still equipped with a dephlegmator and the separation of the head, heart and tail fractions was carried out according to the estimated volume of the distillate. The brandy obtained was submitted to physicochemical analysis by gas chromatography with flame ionization detector. The results showed that all analytical parameters were in compliance with the Brazilian legislation. Regarding the sensory characteristics, the drink presented a clear appearance, with a mild and fruity odor and flavor. DOI: https://doi.org/10.56238/sevened2025.021-081